2020
DOI: 10.1109/tip.2019.2913986
|View full text |Cite
|
Sign up to set email alerts
|

Improving Dataset Volumes and Model Accuracy With Semi-Supervised Iterative Self-Learning

Abstract: Within this work a novel semi-supervised learning technique is introduced based on a simple iterative learning cycle together with learned thresholding techniques and an ensemble decision support system. State-of-the-art model performance and increased training data volume are demonstrated, through the use of unlabelled data when training deeply learned classification models. The methods presented work independently from the model architectures or loss functions, making this approach applicable to a wide range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Carmon et al (2019) proved that using unlabelled data can help to achieve high robust accuracy as well as high standard accuracy at the same time. Dupre et al (2019) considered iteratively pseudo-labelling the whole unlabelled dataset with a confidence threshold and showed that the accuracy converges relatively quickly. Oymak & Gulcu (2021), in which part of our analysis hinges on, studied SSL under the binary Gaussian mixture model setup and characterized the correlation between the learned and the optimal estimators concerning the margin and the regularization factor.…”
Section: Resultsmentioning
confidence: 99%
“…Carmon et al (2019) proved that using unlabelled data can help to achieve high robust accuracy as well as high standard accuracy at the same time. Dupre et al (2019) considered iteratively pseudo-labelling the whole unlabelled dataset with a confidence threshold and showed that the accuracy converges relatively quickly. Oymak & Gulcu (2021), in which part of our analysis hinges on, studied SSL under the binary Gaussian mixture model setup and characterized the correlation between the learned and the optimal estimators concerning the margin and the regularization factor.…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, there have been a few works [173,75,243] involving semi-supervised learning for skin disease diagnosis. Recently, semi-supervised deep learning attracts increasing attention in the field of computer vision and a few successful models have been proposed [244,245,246]. Understanding these models and developing semi-supervised deep learning models specifically for skin disease diagnosis can be a promising direction.…”
Section: Develop Semi-supervised Deep Learning Methods For Skin Disea...mentioning
confidence: 99%
“…In the first place, there is a lack of distinction between the normal skin and the skin lesion. To make segmentation more difficult, variants in skin tones, the presence of ancient artifacts such as hair or ink on the image, air bubbles or ruler marks, non-uniform lighting conditions, the physical location of lesions and variants in lesion colour, crispness, shape, size, and position in the image all contribute to its difficulty [27]. Deep learning algorithms have been used to segment skin lesions in Table…”
Section: Deep Learning Applications In the Detection Of Skin Diseases...mentioning
confidence: 99%